Nursing the sepsis patient- part 2. Issue 9 (18th November 2020) - Foreman, Emma
ABSTRACT: This is the second part of a two-part article outlining the pathophysiology of sepsis and the implementation of a critical care framework to assist veterinary nurses to understand the disease and how to care for these critically ill patients.